Novel methotrexate long-acting system using ambroxol coating and hydroxypropyl methylcellulose encapsulation for preferential and enhanced lung cancer efficiency. - Samaa Abdullah; Najla Altwaijry; Meaad Alnakhli; Ghezlan ALenezi; Alaa A Al-Masud; Hanan Henidi; Yahya F Jamous (PLoS ONE)
Methotrexate (MTX) is classified as an antimetabolite. It's commonly used to treat lung cancer. MTX is an immunosuppressant following the above-mentioned mechanism of action due to its poor selectivity. The tricky move is to investigate the solid dispersions and coating using a co-delivery system of MTX and Ambroxol (ABL). ABL is known for its, anticancer and preferential pulmonary distribution after oral administration. The goals was development were the MTX physiochemical modulation for pulmonary enhanced distribution, MTX resistance modulation and long-acting system development using ABL middle coating and HPMC outer coating. The selection of the optimum MTX-ABL dispersion was done based on the FT-IR characterization. The MTX-release analysis results for the optimized MTX-ABL solid dispersion and the HPMC-coated MTX-ABL gel product were tested for release in the gastrointestinal simulated media to select the most optimum HPMC amounts to coat the MTX-ABL optimum solid dispersion. Moreover, different characterizations of FT-IR, X-ray diffraction and Scanning electron microscopy investigations were completed for the MTX, ABL, the ABL-MTX optimized solid dispersion and the optimum MTX-ABL-HPMC gel. The cytotoxicity assay and the ELISA to assess the levels of BAX, BCL-2, TGF-β and FR-ɑ after the MTX, ABL and the optimized MTX-ABL solid dispersion groups were tested against lung cancer cells, A549 cells, for 24 h. The sustained release character and HPMC-ABL encapsulation of MTX were confirmed. The MTX-ABL solid dispersion showed less MTX resistance without the need to use the high MTX concentrations in comparison to the MTX alone. The apoptotic, anti-metastatic, and MTX preferential lung cancer uptake profiles were higher using the MTX-ABL solid dispersion than in the MTX or ABL. The MTX-ABL-HPMC gel could serve as an alternative to the MTX-oral tablets available in the markets with enhanced efficacy and safety profile.